Rancang Bangun Aplikasi Penentuan Bahan Makanan Bagi Penderita Diabetes Melitus Berbasis Web - Primadiyanto, Ardityo Hari; Sulistiowati, Dosen Pembimbing 1; Lemantara, Dosen Pembimbing 2 Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Diabetes mellitus is serious chronic disease in Indonesia nowdays. This disease can attack all ages and socio-economic. High cost of treatment is one of the obstacle for many diabetics who do not get good and correct treatment. The fee for a consultation for patients with diabetes mellitus are quite expensive. Patients should also take the time to wait in line consultations and sacrificing time for consultation.Solution to these problems is to make a application of determination food ingridients that capable of providing an accurate recommendation food ingridients in accordance to the calculation of nutritional status, the daily caloric needs of patients and determination of the patient's diet. This application of determination food ingridients can help people with diabetes mellitus to determine an appropriate diet with the necessary nutrients diabetics, it can provide modified food ingridients according to the condition of patients and may provide an alternative material other meals if patients do not like the food ingredients recommendation issued by the system